Penggunaan Media Sosial Tiktok Sebagai Referensi Wisata: Studi Kasus Pada Karyawan Indomaret di Jakarta - Widiawanti, Okta; Anom, Erman; Iswadi (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
In the current era, social media through various information content shared plays an important role in many ways. Including the promotion and marketing of tourism destinations. Tiktok is one of the platforms that helps in disseminating a lot of information, from entertainment, shopping, to tourism. The purpose of this study is to determine the benefits of using Tiktok as a platform to find tourist references by Private Employees in Jakarta. The method used in this research is a qualitative method with a case study research type. The data collection techniques used were interview and observation techniques. Interviews were conducted with 4 informants who in this case worked as private employees at one of the minimarkets in Jakarta. The observations made were on the tourist searching activities carried out by the 4 informants above. The results of the research conducted show that content diversity and individual preferences play an important role in the selection of media platforms used to find travel references and other activities. TikTok is one of the media that is useful and can be used as a source of reference and information in the decision to travel by Private Employees in Jakarta. Apart from relying on TikTok media, some Private Employees in Jakarta also rely on other media such as YouTube. Based on this research, it can also be seen that the use of several social media, including platforms such as TikTok, has significantly supported the growth of tourist attractions in Indonesia.